Novel Anatomic Mapping of Pelvic Plexus at Prostatic and Periprostatic Region on Fresh Frozen Cadaveric Setting - Huri, Emre; Sargon, Mustafa F.; Tatar, Ilkan; Aydin, Makbule Cisel; Ezer, Mehmet; Soylemezoglu, Figen (Urology Journal, 2017)
Purpose: We aimed to investigate the exact localization of neural pathway and the frequency of nerve fibers, which are located in the pelvic facial layers in the prostate and periprostatic regions. Materials and Methods: We used four fresh frozen cadavers in this trial. Anatomical layers of anterior rectus fascia and abdominal rectus muscle were dissected to reach the retropubic area. Prostate, visceral and parietal pelvic fascia, levator ani muscle and puboprostatic ligaments were identified. Nine tissue samples, each 1x1 cm in size, were obtained from each cadaver and grouped separately. The locations of these samples are as follows. Group G I from 12 o’clock (apical region), G II from right prostatic apex, G III from 2 o’clock, G IV from right far pelvic lateral, G V from 5 o’clock, G VI from 7 o’clock, GVII from left far pelvic lateral, G VIII from 10 o’clock and G IX from left prostatic apex. Nerve distribution, frequency and diameters of these 9 groups were compared to each other. Results: 36 specimens were obtained from 4 cadavers. Mean number of nerve fibers was 14.1. The number of nerve fibers in each location were not statistically different from each other (P = .9). Mean nerve diameter was 89.1 µm. Mean diameter of nerves was statistically different between groups II, III IV and VI and VIII (P = .001). No difference was seen amongst others. Conclusion: The distributions of nerve fibers at prostate and peri-prostatic region were homogeneous while the nerve diameters varied amongst the different regions.